Wahhdatul Ulum Sebagai Respon dan Solusi Terhadap Dikotomi Keilmuan - Matondang, Abdul Rahman (Islam & Contemporary Issues, 2022)
To understand the meaning behind the Wahdatul Ulum notion as a response to and resolution to the scientific dichotomy is the goal of this study. The reference tracing approach was employed in this investigation. This approach was used to elaborate on the opinions of experts and solid research on wahdatul ulum in more detail. The findings of this investigation suggest; (1) The scientific dichotomy actually creates a wide chasm between general science and religious knowledge, and (2) the current scientific dichotomy is connected to both vertical and horizontal dichotomies as well as factual, ethical, and interpersonal dichotomies. (3) The ambiguity of Islamic education orientation, the discrepancy between the Islamic education system and Islamic teachings, and the disintegration of the Islamic education system are the dangers of scientific dichotomy. (4) Wahdatul Ulum must be capable of integrating with UIN North Sumatra's central philosophical tenet.